2017
DOI: 10.1016/j.wem.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Associated Hyponatremia, Hypernatremia, and Hydration Status in Multistage Ultramarathons

Abstract: The incidence of EAH in multistage ultramarathons was similar to marathons and single-stage ultramarathons, but the cumulative incidence of hypernatremia was 3 times greater than that of EAH. EAH was associated with increased weight gain (overhydration) in early stage nonfinishers and postrace finishers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…The highest number of dehydrated athletes based on their body mass changes (Noakes et al, 2005 ) was found at A 7 . A similar number of athletes were probably dehydrated after a multi-stage ultramarathon in the study of Krabak et al ( 2017 ). Nevertheless, the present runners had a significantly higher percentage change in plasma volume than after A 1 and no relationship between the change in plasma volume and plasma osmolality or fluid intake was found.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The highest number of dehydrated athletes based on their body mass changes (Noakes et al, 2005 ) was found at A 7 . A similar number of athletes were probably dehydrated after a multi-stage ultramarathon in the study of Krabak et al ( 2017 ). Nevertheless, the present runners had a significantly higher percentage change in plasma volume than after A 1 and no relationship between the change in plasma volume and plasma osmolality or fluid intake was found.…”
Section: Discussionmentioning
confidence: 71%
“…Altered hydration status has not been well studied in multi-stage races (Krabak et al, 2017 ). In a multi-stage ultramarathon, athletes often compete for several days (Knechtle et al, 2012a ), run at a slow pace (Costa et al, 2013 ), and are at an increased risk of fluid overload (Rüst et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations